Evidence-based evaluation for stroke guidelines mentioning traditional and complementary medicine rehabilitation - Ran-ran Zhu; Jin-xiang Wang; Bei Pan; Hong-hao Lai; Xiao-ting Xu; Long Ge; Lei Fang (BMC Complementary Medicine and Therapies)
Abstract Background Traditional and complementary medicine (T&CM) is often sought as an significant alternative intervention in stroke prevention and rehabilitation, and is recommended in several guidelines. However, little is known about the quality and consistency of T&CM rehabilitation recommendations for stroke in the guidelines. Methods We systematically searched PubMed, Embase, CNKI, WOS, CBM, Duxiu, Wanfang, VIP, GIN, NICE, NGC, SIGN, BGS, NCCN, WHO guidelines, Google Scholar, MedSci, and Medilive from January 1990 to April 2024 for stroke rehabilitation guidelines that include T&CM recommendations. Our search strategy used search terms related to stroke, complementary and alternative therapy, and CPGs. Four independent reviewers used the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument to evaluate the quality of the included guidelines. We summarized and analyzed the T&CM post-stroke rehabilitation recommendations. Results Nineteen guidelines were included, of which nine were recommended for use according to the AGREE II scores. The highest scores were achieved in the domains of clarity of scope and purpose (90.50% ± 9.99%), while the lowest scores were achieved for applicability (45.56% ± 26.37%). Guidelines commonly recommended acupuncture to improve post-stroke spasticity and dysphagia. However, guidelines recommended against the addition of acupuncture to improve activities of daily living. Additionally, there was still controversy regarding the improvement of upper extremity motor function with acupuncture and specific recommendations for post-stroke cognitive impairment were scarce. Conclusions The quality of stroke rehabilitation guidelines is acceptable, though improvements are needed in some domains, particularly applicability. The recommended guidelines show a high degree of agreement in recommending acupuncture to improve dysphagia after stroke, but recommendations in the areas of upper extremity motor dysfunction and cognitive impairment after stroke need to be further addressed. However, the strength of these recommendations is typically conditional and the level of evidence still needs to be further improved.